2007
DOI: 10.1016/j.febslet.2007.03.046
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor, more than a xenobiotic‐interacting protein

Abstract: The aryl hydrocarbon (dioxin) receptor (AhR) has been studied for several decades largely because of its critical role in xenobiotic-induced toxicity and carcinogenesis. Albeit this is a major issue in basic and clinical research, an increasing number of investigators are turning their efforts to try to understand the physiology of the AhR under normal cellular conditions. This is an exciting area that covers cell proliferation and differentiation, endogenous mechanisms of activation, gene regulation, tumor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
255
0
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(274 citation statements)
references
References 80 publications
8
255
0
5
Order By: Relevance
“…Recent reports have started to elucidate the function of AhR in the absence of any exogenous ligands (Barouki et al, 2007). For example, Hayashibara et al (2003) showed that AhR is constitutively expressed and is active in human adult T-cell leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have started to elucidate the function of AhR in the absence of any exogenous ligands (Barouki et al, 2007). For example, Hayashibara et al (2003) showed that AhR is constitutively expressed and is active in human adult T-cell leukemia.…”
Section: Introductionmentioning
confidence: 99%
“…19,22 Studies using AhR knock-out (AhR Ϫ/Ϫ ) mice have revealed that the AhR plays a role in processes as diverse as cell proliferation, differentiation, migration, development, tissue homeostasis, vasculogenesis, and cancer. [23][24][25][26] From the perspective of TGF␤1 signaling, it is interesting to note that AhR Ϫ/Ϫ mice are prone to develop bile duct fibrosis. 23,25 Candidate endogenous ligands of the AhR include ketocholesterol, bilirubin, indigo, lipoxin A 4 , and tryptophan derivatives such as ITE.…”
mentioning
confidence: 99%
“…1 Aryl hydrocarbon receptor was first discovered as a mediator of dioxin toxicity, but, at present, the AhR pathway is thought to have diverse roles in many cellular functions including the immune system. 2,3 The AhR pathway has been recently shown to be an important regulator of inflammation and immunity. 4,5 For instance, Ahr has an essential role in the negative regulation of the lipopolysaccharide (LPS) signaling pathway through interaction with Stat1.…”
mentioning
confidence: 99%